2019
DOI: 10.1080/03003930.2019.1619554
|View full text |Cite
|
Sign up to set email alerts
|

Which museums to fund? Examining local government decision-making in austerity

Abstract: Please refer to published version for the most recent bibliographic citation information. If a published version is known of, the repository item page linked to above, will contain details on accessing it.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…These include budget rules, there being higher levels of spending in other areas at the beginning of the austerity period, meaning savings were more readily identifiable in these areas, and the imperative to maintain services delivered from buildings which can be repurposed towards income-generation. Moreover, previous research has argued that decisions about expenditure on "Culture and Heritage" are unlikely to involve those who work in these services (Lawley, 2003;Rex, 2020b), raising the possibility that being the least affected subcategory is an unintended consequence of decisions taken elsewhere and in relation to other services rather than evidence of the agency and intentionality of advocates for spending on certain forms of culture. As such, although our analysis tallies with existing findings that discretionary services have been the most common target of austerity cuts (Streeck, 2014;Gray and Barford, 2018), we found that this interpretation requires nuance when it comes to the "Culture and Heritage" subcategory as by some measures, services in the "Other" subcategory (libraries, open spaces, tourism) have experienced a much steeper decline when set against "Culture and Heritage".…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include budget rules, there being higher levels of spending in other areas at the beginning of the austerity period, meaning savings were more readily identifiable in these areas, and the imperative to maintain services delivered from buildings which can be repurposed towards income-generation. Moreover, previous research has argued that decisions about expenditure on "Culture and Heritage" are unlikely to involve those who work in these services (Lawley, 2003;Rex, 2020b), raising the possibility that being the least affected subcategory is an unintended consequence of decisions taken elsewhere and in relation to other services rather than evidence of the agency and intentionality of advocates for spending on certain forms of culture. As such, although our analysis tallies with existing findings that discretionary services have been the most common target of austerity cuts (Streeck, 2014;Gray and Barford, 2018), we found that this interpretation requires nuance when it comes to the "Culture and Heritage" subcategory as by some measures, services in the "Other" subcategory (libraries, open spaces, tourism) have experienced a much steeper decline when set against "Culture and Heritage".…”
Section: Discussionmentioning
confidence: 99%
“…Situating current spending patterns in their organisational and institutional contexts, albeit in an exploratory way, is an important concern of this article due to the relative neglect of the influence of these contexts on decision-making processes and outcomes (cf. Gray, 2002;Rex, 2020b). This is in spite of a long tradition of such approaches in political science where explanations based on individual choice have been met with approaches seeking to explore the interaction between individuals and institutions (Lowndes, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Changes occurring in local government have highlighted the difficulty of adjusting service delivery to fluctuating sources of national funding. Recent scholarship has emphasised on the necessity of institutional resilience among local public services in order to endure austerity (Gardner, 2017;Rex, 2019). To some scholars, the new wave of decentralized decision-making has prompted large and small administrative units to restructure, yet, in many places, the reshuffling of people and resources strays little from existing arrangements (Richardson, Durose and Dean, 2018).…”
Section: Decentralisation and Central-local Relationsmentioning
confidence: 99%
“…The days are over when museums could legitimise their place in society simply by referring to the traditional functions of collecting, researching and disseminating (Black 2012, Achiam & Sølberg 2017. Today, urges for museums to clarify their contributions to broader society come from many different sources: governments, who may allocate funding based on an institution's potential to generate financial returns (Rex 2019) or public health benefits (Desmarais et al 2018); historians and indigenous experts, who critique the colonialist structures that enable museums to retain property rights to objects looted from former colonies (Knott 2018, Bakare 2019, Owen 2020; or scholars of cultural history, who demand that the white, western, male gaze prevalent in many exhibitions be replaced with a more diverse range of perspectives (Levin 2010, Robinson 2017, Balle 2019.…”
mentioning
confidence: 99%